The impact of widowhood on household consumption among middle-aged and older adults: evidence from China - Jiao, Xianfu; Peng, Lijin; Si, Xu; Yang, Xujin (Frontiers in Public Health, 2025)
BackgroundAs China enters a phase of accelerated population aging, the number of individuals aged 65 and above had surpassed 217 million by the end of 2023, accounting for approximately 15.38% of the total population. This demographic shift has triggered an unprecedented wave of social challenges. While birth, aging, illness, and death are the natural parts of human life, widowhood functions as an “invisible threat” to the well-being of middle-aged and older adults. Accordingly, this paper investigates the impact of widowhood on household consumption among middle-aged and older adults, along with the underlying mechanisms.MethodsThis paper utilizes data from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2020, and applies a difference-in-differences (DID) approach to assess the impact of widowhood on household consumption among middle-aged and older adults. Heterogeneity analysis is conducted based on household head characteristics and consumption structure to explore the differential impacts of widowhood. Moreover, the mechanisms are analyzed through three mechanisms: income, psychological consumption, and household saving rate.ResultsWidowhood leads to a reduction in household consumption among middle-aged and older adults. However, the magnitude of this decline is relatively modest. Heterogeneity analysis reveals that widowhood exerts a significantly adverse impact on rural households, whereas no significant effect is observed among urban households. The negative effect on consumption is more pronounced among middle-aged individuals than among older adults. The reduction in medical expenditures caused by widowhood is greater than that in non-medical consumption. Mechanism analysis indicates that widowhood directly reduces household consumption by lowering income and increasing psychological consumption, while indirectly reducing consumption by raising the household saving rate.ConclusionWidowhood negatively affects household consumption among middle-aged and older adults, primarily due to reduced income. It is therefore recommended to enhance the social security and psychological support systems, strengthen income and healthcare protection for rural middle-aged and older adults in a context-sensitive manner, and promote scientific household saving strategies to mitigate widowhood-related risks.